Phage community involvement in fermented beverages: an open door to technological advances?. Issue 17 (26th September 2021) - Ledormand, Pierre; Desmasures, Nathalie; Dalmasso, Marion
Abstract: Bacteriophages (phages) are considered the most abundant biological entities on Earth. An increasing interest in understanding phage communities, also called viromes or phageomes, has arisen over the past decade especially thanks to the development and the accessibility of Next Generation Sequencing techniques. Despite the increasing amount of available metagenomic data on microbial communities in various habitats, viromes remain poorly described in the scientific literature particularly when it comes to fermented food and beverages such as wine and cider. In this review, a particular attention is paid to the current knowledge on phage communities, with a special focus on fermented food viromes and the methodological tools available to undertake their study. There is a striking lack of available data on the fermented foods and beverages viromes. As far as we know, and although a number of phages have been isolated from wine, no general study has to date been carried out to assess the diversity of viromes in fermented beverages and their possible interactions with microbiota throughout the fermentation process. With the aim of establishing connections between the currently used technologies to carry out the analysis of viromes, possible applications of current knowledge to fermented beverages are examined.